Not by order, nor by dialogue: the metanoetic presence of the kingdom of God in a fluid new world and church - S. Joubert (Acta Theologica)
Fluid modernity favours new forms of individualism, complexity and non-linear change. Therefore, the emphasis on order, predictability and open dialogue in religious circles, as preferred ways of responding to change and problems, must be augmented by a metanoetic understanding of the kingdom of God. As a subversive, upside-down new reality, God’s kingdom is relationally driven, open-ended and in constant flux. Through “metanoia,” as the urgent boundary-crossing call of Jesus, individuals become part of this subversive new world where selfless love for God and others dominates. As an ongoing process of personal metamorphosis, “metanoia” simultaneously facilitates new forms of “complexity leadership”, where religious leaders turn into sages who create fluid new structures to facilitate familial relationships and a new culture of respect in which believers are allowed to thrive in their Spirit-induced flow states.